Analisis Dampak Rehabilitasi Hutan dan Lahan Di DAS Mikro Tosoa dan Tuguaer Sub DAS Ake Leije Mata Kabupaten Halmahera Barat - Muhammad Yusril; Adnan Sofyan; Ramli Hadun (Jurnal Pertanian Khairun, 2022)
Forest and land rehabilitation (RHL) is a strategic program of the government in the field of forestry development. RHL aims and objectives to restore, maintain, and improve the function of forests and lands to be maintained. The study aimed to analyze the impact of RHL activities in the Tosoa Micro Watershed and the Ake Leije Mata Sub-Watershed Tuguaer, South Mother District, West Halmahera Regency. The assessment of planting success was carried out with a systematic sampling technique with random start with a sampling intensity of 5% on each planting plot at the Micro Watershed RHL site. The plant assessment plot is rectangular (40 m x 25 m) with a distance between the measuring plots for the North – South direction of at least 200 m while the East – West direction is at least 100 m. The data collected is in the form of primary data and secondary data. Data on the assessment of planting success were analyzed by descriptive and estimating methods. The results of the analysis are classified into the criteria for successful planting, while the impact analysis shown to determine erosion and sedimentation. The results showed that in general, the success rate of planting in the Tosoa and Tuguaer RHL Micro Watersheds carried out in 2019 - 2021 was classified as successful. The percentage of successful planting in the Micro RHL watershed of the Tosoa protected forest block and Planting Monument (P0), First Year Maintenance (P1), and Second Year Maintenance (P2) respectively was 82.27%, 79.55% and 76.08%. The average growth of RH plants in the Micro watershed of the Tosoa protected forest block and Planting Tuguaer (P0), First Year Maintenance (P1) and Second Year Maintenance (P2) respectively by 49 cm, 52 cm and 55.16%. Prediction of Erosion Value in the Tuguaer Block RHL Micro Watershed (145.57 tons / ha / th); and the Tosoa Block (90.59 tons/ha/th) and the predicted sediment value of the Tuguaer Block (50.89 tons/ha/th); and Tosoa Block (24.41 tons/ha/th).Keywords : Rehabilitation, Success, Micro Watershed, Erosion, Sedimentation.